Empirical investigation of exchange rate transmission into general inflation level in Ethiopia – SVAR approach - Henok Ezezew Sheferaw; Kalid Wendimnew Sitotaw (Cogent Business & Management, 2023)
Examining the extent of exchange rate pass-through (ERPT) to domestic prices has substantial significance for policymaking given the ongoing devaluation of the Ethiopian currency. This study aimed to investigate the impact of exchange rate pass-through (ERPT) on domestic prices in Ethiopia between 1975 and 2020, using recursive structural vector autoregressive (SVAR) analysis. The results revealed that a unit change in the nominal effective exchange rate (appreciation) was associated with a reduction of 0.059 in consumer prices after 1 year, indicating that ERPT to domestic inflation in Ethiopia is significant, but incomplete and temporary. Additionally, impulse response and variance decomposition analyses revealed that government expenditure and international energy prices had an expanding effect on domestic prices. Therefore, the policy implications of the study include measures to stabilize and control the exchange rate, promote domestic production, reduce reliance on imported goods, and explore alternative energy sources and transportation methods.
Keywords: 650; domestic price; ERPT; Ethiopia; SVAR